2007
DOI: 10.2337/db06-1018
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of Transforming Growth Factor (TGF)-β1 in the Induction of Postglomerular Albuminuria in Diabetic Nephropathy

Abstract: Transforming growth factor-␤ (TGF-␤) has previously been implicated in the progression of diabetic nephropathy, including the onset of fibrosis and albuminuria. Here we report for the first time the use of a high-affinity TGF-␤1 binding molecule, the soluble human TGF-␤ type II receptor (sT␤RII.Fc), in the treatment of diabetic nephropathy in 12-week streptozotocin-induced diabetic Sprague-Dawley rats. In vitro studies using immortalized rat proximal tubule cells revealed that 50 pmol/l TGF-␤1 disrupted albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 53 publications
4
86
0
Order By: Relevance
“…The hypertrophy of the kidney in the diabetic rat was associated with a marked increase in the urinary excretion of TGF-␤, a factor that is involved in growth and proliferation and cellular differentiation and which has been implicated in some of the renal manifestations of diabetes (26,28). Increased TGF-␤ gene expression has been reported for the BB rat and the NOD mouse, models of type 1 diabetes (29), and TGF-␤ protein expression was increased in glomeruli from a patient with diabetes (30).…”
Section: Discussionmentioning
confidence: 99%
“…The hypertrophy of the kidney in the diabetic rat was associated with a marked increase in the urinary excretion of TGF-␤, a factor that is involved in growth and proliferation and cellular differentiation and which has been implicated in some of the renal manifestations of diabetes (26,28). Increased TGF-␤ gene expression has been reported for the BB rat and the NOD mouse, models of type 1 diabetes (29), and TGF-␤ protein expression was increased in glomeruli from a patient with diabetes (30).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, Ang II has been shown to induce marked glomerular sclerosis 27 with cell proliferation of the glomerular mesangium, 28 vascular endothelium, 29 tubular epithelium 30 and the vascular smooth muscle. 31 Ang II causes podocyte injury by increasing glomerular capillary pressure through a selective constriction of efferent arterioles. 32,33 In addition, Ang II is thought to act directly on podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…3). Decreased megalin expression in PTCs has been observed in the early diabetic stages of experimental animals (Tojo et al 2001;Russo et al 2007), and it has been suggested that the functions of megalin are also impaired in patients during the early stages of diabetic nephropathy, since low molecular weight proteinuria is frequently observed in patients at these stages (Pontuch et al 1992;Hong et al 2003). Therefore, the altered regulation of megalin expression and its functions must be primarily responsible for the early development of proteinuria/albuminuria in diabetic patients.…”
Section: Megalinmentioning
confidence: 99%